2019
DOI: 10.1186/s12913-019-3888-5
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-identified patient care and health services research priorities in the United Arab Emirates: a Delphi study

Abstract: BackgroundThe need for improved research on ill health has been recognized internationally and locally in the United Arab Emirates (UAE). The UAE Nursing and Midwifery Council recently committed to enhancing the status and contributions of nursing in healthcare research across the UAE by establishing a National Committee for Research Development. This study using a Delphi method to identify research priorities from the perspective of nurses delivering frontline healthcare.MethodsA two-phase Delphi design was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…The result of this study and the previous study, which reviewed the current research status (McCreaddie et al, 2018) and the priorities of nursing research in UAE (Al-Yateem et al, 2016, 2018, 2019, form the basis of the future UAE Nursing and Midwifery Council nursing research strategy. The Subcommittee looks forward to reporting on future initiatives to ensure the nursing profession continues to influence and enhance health care policy and practice in the UAE.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The result of this study and the previous study, which reviewed the current research status (McCreaddie et al, 2018) and the priorities of nursing research in UAE (Al-Yateem et al, 2016, 2018, 2019, form the basis of the future UAE Nursing and Midwifery Council nursing research strategy. The Subcommittee looks forward to reporting on future initiatives to ensure the nursing profession continues to influence and enhance health care policy and practice in the UAE.…”
Section: Resultsmentioning
confidence: 93%
“…Finally, this study in highlighting the barriers to research identified by study participants has added great value to the previous studies done in the UAE about nursing research. To conclude, having identified the current status of nursing research in UAE (McCreaddie et al., 2018), the barriers to conduct and utilize research, and the priorities of nursing research in UAE (Al-Yateem et al., 2018, 2019), the stage is set to work out a strategy to move the nursing research agenda forward in the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies relating to HSR describe its application to a specific medical condition rather than the broader health system [21][22][23]. developed Previous paediatric HSR agendas have primarily been conceptual models, have demonstrated limited engagement or integration in the health "system" and are specific to the United States [12,24,25].…”
Section: Comparison With Previous Hssr Agendasmentioning
confidence: 99%
“…producing competent nurses who can practise globally) (Mckinnon, Mcnelis, Leon, Whitlow, & Fitzpatrick, 2019; Mcnelis & Mckinnon, 2019; Palmer & Miles, 2019) and the role of technology in education (Broadbent, 2017; Thomas, West, & Borup, 2017). UAE‐based discussions regarding these aspects are still in the early stages, and they remain to be achieved in nursing education (Al‐Yateem et al, 2019; Brownie, Hunter, Aqtash, & Day, 2015; Brownie, Rossiter, Hamad, & Aqtash, 2017; El‐Haddad, 2006; Gomez, 2010; Johnson, 1992; Kronfol & Athique, 1986; McCreaddie et al, 2018; Nematollahi & Isaac, 2012; Torres‐Alzate, 2019). This suggests the road map for the UAE nursing education system needs to be strengthened.…”
Section: Nursing Leadership and Management Challengesmentioning
confidence: 99%